Utilization of vegetables oils in diets for piava juveniles (Leporinus obtusidens) - Adorian, Taida Juliana; Mombach, Patrícia Inês; Pianesso, Dirleise; Uczay, Juliano; Decarlli, Junior; Lazzari, Rafael (Revista de Ciências Agroveterinárias, 2017)
This study aimed to evaluate the response of piava (Leporinus obtusidens) after the use of vegetable oils in the diet, under performance, nutrient deposition and activity of digestive enzymes. Over 35 days five treatments were tested, with the inclusion of 3% of corn oil, soy, canola, linseed, and a control treatment without the inclusion of oil. Fish with an average initial weight of 1.78±0.07 g were randomly assigned in a water recirculation system consisting of 15 tanks, with suitable water quality parameters throughout the trial period. At the end of biometrics experiment data was collected. The experimental design was completely randomized, with five treatments and three replicates; the data was submitted to normality test and analysis of variance. The averages, when significant, were compared by Tukey test (p<0.05). Fish fed diets containing canola oil showed higher weight and length and protein deposition when compared to the control treatment. Higher chymotrypsin activity was observed in the fish fed the diet containing soya oil and lower with linseed oil. It is concluded that the use of oils in the diet is essential for best performance of the fish, and canola oil as indicated by optimizing the deposition of body protein for animals.